Dendritic Cells: Cellular Mediators for Immunological Tolerance - Chun Yuen J. Chung; Dirk Ysebaert; Zwi N. Berneman; Nathalie Cools (Clinical and Developmental Immunology)
In general, immunological tolerance is acquired upon treatment with non-specific immunosuppressive drugs. This indiscriminate immunosuppression of the patient often causes serious side-effects, such as opportunistic infectious diseases. Therefore, the need for antigen-specific modulation of pathogenic immune responses is of crucial importance in the treatment of inflammatory diseases. In this perspective, dendritic cells (DCs) can have an important immune-regulatory function, besides their notorious antigen-presenting capacity. DCs appear to be essential for both central and peripheral tolerance. In the thymus, DCs are involved in clonal deletion of autoreactive immature T cells by presenting self-antigens. Additionally, tolerance is achieved by their interactions with T cells in the periphery and subsequent induction of T cell anergy, T cell deletion, and induction of regulatory T cells (Treg). Various studies have described, modulation of DC characteristics with the purpose to induce antigen-specific tolerance in autoimmune diseases, graft-versus-host-disease (GVHD), and transplantations. Promising results in animal models have prompted researchers to initiate first-in-men clinical trials. The purpose of current review is to provide an overview of the role of DCs in the immunopathogenesis of autoimmunity, as well as recent concepts of dendritic cell-based therapeutic opportunities in autoimmune diseases.